Utilization of Leucaena Leaves Meal Gung (Leucaena Leucocephala) Fermented by Aspergillus niger as Subtitution of Soybean Meal in The Diets on The Growth of Thai Cat Fish (Pangasius Hypophthalmus) - Raudah, Peggi; Suharman, Indra; Alawi, Hamdan (Fakultas Perikanan dan Kelautan Universitas Riau, 2018)
The research was conducted for 60 days from April to June 2017. The aim of this research was to know the utilization of fermented leucaena leaves meal as a substitution of soybean meal in the diets on the growth and feed efficiency of Thai Catfish. Completely randomized design (CRD) was used in this experiment, with one factor, five level treatment and three replications. Fish were reared in 1 m3cages with stocking density 20/cages. Feeding trial were replacing soybean meal with fermented leucaena leaves meal applied to P1 (0%), P2 (25%), P3 (50%), P4 (75%), and P5 (100%). The fish used in this research with 2,13 ± 0,39g of weight. The result of this research showed that fermented leucaena leaves meal has significant effect (P>0,05) on growth and feed efficiency of Thai Catfish. Diets which contains 75% of fermented leucaena leaves meal and 25% of soybean meal (P4) produce the highest specific growth rate (4,11%/day), feed efficiency (62,6%), feed digestibility (59,45%), and protein retention (18,85%). Based on the result of this study conclude that fermented leucaena leaves meal can be used as substitution for soybean meal in diets of Thai Catfish.